Transactional demand for central bank digital currency - Luca Nocciola; Alejandro Zamora-Pérez (European Central Bank (ECB), 2024)
We shed light on the demand for a central bank digital currency (CBDC) as a means of payment, based on survey payment data. We provide a quantitative framework to assess transactional demand for CBDC at the point of sale, accommodating a wide range of design choices. We develop a structural model of payment means adoption and usage and estimate CBDC demand based on individuals' preferences for payment method attributes. We disentangle the friction potentially associated to CBDC adoption, assessing two of its potential drivers: information frictions and gradual diffusion of digital payment methods. We find that modelling adoption is key to understanding CBDC demand. Finally, we show that optimal CBDC design, information campaigns, and network effects can substantially boost demand.
Keywords: E41; E42; E47; 330; CBDC; Money demand; Payments; Structural model; Random utility